2013
DOI: 10.1109/jsen.2013.2271585
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Sucking Monitoring of Newborns

Abstract: This version is available at https://strathprints.strath.ac.uk/44084/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Microneurography and sEMG signals were recorded at a sampling rate of 10,000 Hz with a 16-bits data acquisition board (National Instruments PCI-6251), installed on a personal computer (PC) running a custom program written in Labview 2012 that handled the recording and the real-time processing assisting the neurologist in seeking the fibers. The pressure sensor was custom-made [24] and constituted by an airtight sphere-catheter system connected to a Programmable Interface Controller at its turn connected to the PC by a serial port. The recording of its data was performed at a sampling rate of 10 Hz and controlled by the aforementioned custom program.…”
Section: Methodsmentioning
confidence: 99%
“…Microneurography and sEMG signals were recorded at a sampling rate of 10,000 Hz with a 16-bits data acquisition board (National Instruments PCI-6251), installed on a personal computer (PC) running a custom program written in Labview 2012 that handled the recording and the real-time processing assisting the neurologist in seeking the fibers. The pressure sensor was custom-made [24] and constituted by an airtight sphere-catheter system connected to a Programmable Interface Controller at its turn connected to the PC by a serial port. The recording of its data was performed at a sampling rate of 10 Hz and controlled by the aforementioned custom program.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 reports a typical 10 s pressure burst: experimental data, acquired on healthy subjects and reported in [ 23 ], showed that intraoral pressure is in the range of [−140,+15] mmHg. The bandwidth of the pressure signal was estimated, calculating its Power Spectral Density (PSD) by means of the Welch overlapped segmented average: it may be considered well below 20 Hz.…”
Section: Nutritive Sucking Processmentioning
confidence: 99%
“…Each suck is composed of an Increasing Suction (IS) phase, followed by a change in pressure in the opposite direction giving a Decreasing Suction (DS) phase [3]. The bandwidth of the pressure signal can be considered below 20 Hz according to previous results obtained from the analysis of the Power Spectral Density, reported in [12]. Thus, pressure signals have been low-pass filtered with a cut-off frequency equal to 20 Hz.…”
Section: Signal Analysismentioning
confidence: 99%